Portable Multi-Inputs Renewable Energy System for Small Scale Remote Application - Al-Bahadly I (Scientific Research Publishing Inc)
This paper presents a potable renewable energy system. The portable renewable energy power unit is designed from a need. The need is for first response teams in remote natural disaster situations to have a reliable source of energy to power a small vaccine refrigerator or water purification system and a basic satellite communication system. It is important that such a need is explored as a practical solution has the potential to save the lives of people in remote areas, who would otherwise suffer from a lack of humanitarian aid. Currently diesel generators are the primary source of electricity generation for disaster responders and in most situations work very well and provide a sufficient amount of electricity to meet the power needs. However, in remote areas road infrastructure is often damaged. In this type of situation getting a constant supply of diesel to the area is an expensive or impractical operation. This is where the portable renewable energy power unit bridges the gap and allows a more practical solution to be implemented. The specific aim of the work is to design a compact, stand-alone, product that can be easily transported by people across uneven terrain. It can generate power from wind, solar and hydro energy sources. In this work a new non-isolated multiport DC-DC converter topology for a hybrid energy system in low power applications is proposed. The new topology assimilates multiple renewable energy sources and power up multiple loads with different output levels. A complete Solid works model and FEA analysis, on required components, is completed. The scope of the work encompasses both the electrical and mechanical design of the system.
Keywords: 0906 Electrical and Electronic Engineering; 0913 Mechanical Engineering